Calcium handling precedes cardiac differentiation to initiate the first heart beat - Tyser, R; Miranda, A; Chen, C; Davidson, S; Srinivas, S; Riley, P (eLife Sciences Publications, 2016)
The mammalian heartbeat is thought to begin just prior to the linear heart tube stage of development. How the initial contractions are established and the downstream consequences of the earliest contractile function on cardiac differentiation and morphogenesis have not been described. Using high-resolution live imaging of mouse embryos, we observed randomly distributed spontaneous asynchronous Ca2+-oscillations (SACOs) in the forming cardiac crescent (stage E7.75) prior to overt beating. Nascent contraction initiated at around E8.0 and was associated with sarcomeric assembly and rapid Ca2+ transients, underpinned by sequential expression of the Na+-Ca2+ exchanger (NCX1) and L-type Ca2+ channel (LTCC). Pharmacological inhibition of NCX1 and LTCC revealed rapid development of Ca2+ handling in the early heart and an essential early role for NCX1 in establishing SACOs through to the initiation of beating. NCX1 blockade impacted on CaMKII signalling to down-regulate cardiac gene expression, leading to impaired differentiation and failed crescent maturation.